Cross-Section Homogenization for Reactivity-Induced Transient Calculations. Issue 6 (18th September 2016) - Dugan, K.; Zmijarevic, I.; Sanchez, R.
ABSTRACT: Current practice in accident simulation is to use homogenized cross-sections that are computed using a critical flux. It is shown, however, that using critically homogenized cross-sections in prompt kinetic calculations can induce large errors in the calculation (∼20% in Max Power). This work presents two alternative methods for homogenization that are shown to improve these errors (∼1% in Max Power). The first method uses a time-integrated flux from a multiphysics solution, while the second uses an asymptotic solution to the time-dependent transport equation to homogenize cross-sections. The new methods are applied to several reactivity insertions in an infinite homogeneous medium and are also shown to work well with different homogenized group structures having two, three, and six energy groups. The introduction of delayed neutron precursors is treated, including possible modifications to the asymptotic solution homogenization method. Additionally, it is observed that cross-sections computed using a critical flux may perform adequately for transients where the reactivity insertion is small (ρ < β).